1980
DOI: 10.1007/bf00421196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatigue on the series elastic component of human muscle

Abstract: The effects of fatigue on the muscular series elastic component were studied in man. The compliance-force relationship (K-F) of the fatigued muscle was compared with that of the unfatigued muscle. The K-F relationships were established under electromyographic control in two cases: 1. The F variation came from the decrease in maximum voluntary force appearing in fatigue which was produced by rhythmic flexions against an elastic resistance. The compliance was measured at regular intervals as fatigue developed. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…While our pre-fatigue values do not support this contention (further suggesting reflex induced EMD mechanisms may be different from voluntary contractions), it is possible that fatigue may interact with these factors to differentially influence the compliance of the series elastic component. Increased muscle compliance following fatigue has been previously demonstrated by Vigreux et al [55].…”
Section: Series Elastic Componentmentioning
confidence: 80%
“…While our pre-fatigue values do not support this contention (further suggesting reflex induced EMD mechanisms may be different from voluntary contractions), it is possible that fatigue may interact with these factors to differentially influence the compliance of the series elastic component. Increased muscle compliance following fatigue has been previously demonstrated by Vigreux et al [55].…”
Section: Series Elastic Componentmentioning
confidence: 80%
“…It has also been shown that the contractile mechanisms of a muscle, especially the series elastic component, may be altered during an exercise (Vigreux et al 1989) and it is assumed that the contractile response of a muscle depends to a great extent on the exercise activation (Rassier and MacIntosh 2000). A brief period of repetitive stimulation results in enhanced contractile response (potentiation) while continued stimulation results in impairment or attenuated response (fatigue) (Rassier and MacIntosh 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For "ramp contractions", once any value (corresponding to a 1 mm ϫ 1 mm subregion) within the ROI reached 266 kPa, there was no further analysis at that force and any higher force. For experiment I, the EMG-RMS/torque and shear elastic modulus/ torque relationships obtained for "ramp contractions" were fitted to a linear model (4,34) to calculate slope (a) and y-intercept (b). To assess the fit for the first ramp, the coefficient of determination (R 2 ) and the error of estimation [i.e., RMS deviation (RMSdevR1)] were calculated for both EMG and SSI measurements (4).…”
Section: Index Of Muscle Force During a Fatiguing Task • Bouillard K mentioning
confidence: 99%
“…Thus one would expect that the alteration of motor unit discharge characteristics associated with fatigue does not influence the shear elastic modulus. However, putative changes in mechanical properties of muscle occurring with fatigue (31,34,35) could preclude the ability to provide an index of muscle force during a fatiguing contraction.…”
mentioning
confidence: 99%